PENANAMAN PEMAHAMAN KONSEP SEGITIGA MELALUI PEMBELAJARAN GEOMETRI MENGGUNAKAN GEOBOARD - Lorantifolia Turian; Mohammad Rif’at; Rustam Rustam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to determine the process and results of imparting an understanding of the triangle concept using geoboard as an instructional media. It was qualitative research with a case study method. The data sources in this study were one student (as a case subject), two mathematics teachers, and one mathematics lecturer. Data collection techniques used were personal interviews, observation, questionnaires, and documentation. Data analyzed by three steps: reduction, presentation, and verification. Research findings indicate that geoboard has a relationship with abstract concepts and concrete objects. The geoboard could be used as support while learning the triangle concept in Geometry. The more exercises raised through the geoboard more embedded the triangle concept in student's understanding. Based on the results of this study, the researcher concluded that the geoboard is an alternative instructional media in triangle learning. It recommends that learning mathematics could increase the understanding of concepts in the future. Keywords: Geoboard, Imparting of Concepts, Instructional Media, Triangle